Values of Character Education Contained in Wayang Beber Pacitan Performance - Margana, Margana; Rohendi Rohidi, Tjetjep; Iswidayati, Iswidayati; Sony Kartika, Dharsono (Universitas Negeri Semarang, 2018)
Wayang beber is a unique and rare type of traditional arts in Nusantara but its existence is now threatened with extinction. This study aimed to determine the values contained in the Wayang Beber Pacitan show. This research was descriptive qualitative. The data were collected using observation techniques, interviews, and document studies. The samples were selected using purposive sampling technique. The data were then analyzed using interactive analysis method and validated using a triangulation technique. The results of this study indicate that as a traditional art in Nusantara, wayang beber has its own uniqueness when compared with other types of puppets. The uniqueness of wayang beber is in the form and the way of its performance; it is in the form of paintings and the puppet is performed by means of unfolding it. Then it is told by the puppeteer in accordance with the contents of the story. The story in wayang beber contains the values of character education which is very important for the supporting community. These values, among others, are the value of responsibility, loyalty, devotion, nationality, and tenacity in reaching the ideals.